The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.est.7b03085
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Amplicon Sequencing Reveals Significant Changes in Microbial Compositions during Cyanobacteria-Laden Drinking Water Sludge Storage

Abstract: This is the first study to systematically investigate the microbial community structure in cyanobacteria-laden drinking water sludge generated by different types of coagulants (including AlCl, FeCl, and polymeric aluminum ferric chloride (PAFC)) using Illumina 16S rRNA gene MiSeq sequencing. Results show that Cyanobacteria, Proteobacteria, Firmicutes, Bacteroidetes, Verrucomicrobia, and Planctomycetes were the most dominant phyla in sludge, and because of the toxicity of high Al and Fe level in AlCl and FeCl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Analysis of relative abundance of the bacterial community at the phylum level, based on high throughput sequencing data, showed that Proteobacteria, Actinobacteria, Cyanobacteria, Bacteroidetes, Firmicutes and Verrucomicrobia were the six most abundant phyla throughout the sampling period (Figure 1a). As expected, Proteobacteria was by far the most abundant phylum at the beginning of the sampling period (1 August) as has been observed by Pei et al (2017) [36]. The high relative abundance of Proteobacteria, especially in the beginning of sampling and Bacteroidetes at the end of the sampling period, may indicate contamination of the sampling point with human/animal-associated fecal markers [39][40][41].…”
Section: Variation Of the Cyanobacterial Bloom Compositionsupporting
confidence: 75%
See 2 more Smart Citations
“…Analysis of relative abundance of the bacterial community at the phylum level, based on high throughput sequencing data, showed that Proteobacteria, Actinobacteria, Cyanobacteria, Bacteroidetes, Firmicutes and Verrucomicrobia were the six most abundant phyla throughout the sampling period (Figure 1a). As expected, Proteobacteria was by far the most abundant phylum at the beginning of the sampling period (1 August) as has been observed by Pei et al (2017) [36]. The high relative abundance of Proteobacteria, especially in the beginning of sampling and Bacteroidetes at the end of the sampling period, may indicate contamination of the sampling point with human/animal-associated fecal markers [39][40][41].…”
Section: Variation Of the Cyanobacterial Bloom Compositionsupporting
confidence: 75%
“…Planktothrix, Microcystis and Cyindrospermopsis were the most abundant genera and were positively correlated with the nutrient levels in raw water. Pei, Xu [36] used 16S rRNA sequencing to study the shifts in the microbial community in clarifier sludge following coagulation by FeCl 3 , AlCl 3 and PAFC (Polyaluminium Ferric Chloride). Results revealed selective removal of the different bacterial species, as the relative abundance of the Microcystis, Rhodobacter, Phenylobacterium and Hydrogenophaga decreased in AlCl 3 sludge compare to the FeCl 3 and PAFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cyanobacteria‐laden drinking water sludge, the relative abundance of the dominant genera Microcystis , Rhodobacter , Phenylobacterium and Hydrogenophaga clearly decreased when treated with 20 different types of coagulants (Pei et al ., 2017). Through the results of the present study, it can be reported for the first time that Phenylobacterium had correlations with toxic cyanobacteria ( Microcystis ) in the field, and these interactions were verified in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of cyanotoxins in the sludge is complex due to the simultaneous occurrence of various phenomena such as cell survival, growth, lysis, cell-bound cyanotoxin release, and released cyanotoxin degradation [53][54][55][56]59,106,107]. Based on the increased risk of cell lysis and cyanotoxin release during sludge storage, some studies have suggested that cyanobacteria-laden sludge should be disposed of prior to 4 days to avoid metabolite release [47,51,108]. However, these studies only focused on metabolite release and not on cell survival/growth phenomena.…”
Section: Sludge Handling Challengesmentioning
confidence: 99%